2019
DOI: 10.1007/s12040-019-1227-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the genesis and landfall locations of tropical cyclones over the Bay of Bengal in the current global warming era

Abstract: Trends in tropical cyclone (TC) genesis and landfall over the Bay of Bengal (BOB) were analysed to identify global warming and climate change impacts. The historical TC data for the period 1901-2015 available through the cyclone eAtlas from India Meteorological Department were used. The analysis was confined to the 3-month period from October to December when the maximum number of TCs occurs over the BOB. Analysis was conducted for the two 50-yr periods of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Also, several recent studies using TC track data have been conducted in the Northern Hemisphere (e.g. Bell et al 2020;Bhaskar Rao et al 2019;Ge and Colle 2019;Kelly et al 2018;Liu et al 2019;Zhang et al 2020). However, whilst historical records of TC tracks, as recorded by geospatial location, have the potential to yield new insight into TC behaviour, the body of research into TC track spatial geometry and curvature and the evolution of these characteristics post-genesis is far less prevalent (Sharma et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, several recent studies using TC track data have been conducted in the Northern Hemisphere (e.g. Bell et al 2020;Bhaskar Rao et al 2019;Ge and Colle 2019;Kelly et al 2018;Liu et al 2019;Zhang et al 2020). However, whilst historical records of TC tracks, as recorded by geospatial location, have the potential to yield new insight into TC behaviour, the body of research into TC track spatial geometry and curvature and the evolution of these characteristics post-genesis is far less prevalent (Sharma et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Balaji et al (2018) also indicated that there is a 34% rise in the frequency and also a 37% rise in duration of VSCS category in the NIO region based on the 1997-2014 period dataset. A significant eastward shift was also noted in TC genesis locations in the BOB region during post-monsoon seasons of this period-which tends to enhance the vulnerability for the coastal regions of Bangladesh (see also Rao et al 2019).…”
Section: Historical Changesmentioning
confidence: 82%
“…Numerous examples of Southern Hemisphere TC activity analysis (including the South Pacific) using historical cyclone track data exist in recently published scientific literature (e.g., Magee, Verdon-Kidd, Diamond, & Kiem 2017;Bell, Chand, & Turville 2020;Chand et al 2019; (Ramsay, Camargo, & Kim, 2012); Magee, Lorrey, Kiem, & Colyvas 2020;Sharma, Verdon-Kidd, & Magee 2020, 2018Zhao, Zhan, Wang, & Xu 2018). Also, many recent studies using TC track data have been conducted in the Northern Hemisphere (e.g., Bell et al 2020;Bhaskar Rao, Srinivas, & Satyanarayana 2019;Ge & Colle 2019;Kelly et al 2018;Liu, Pan, Huang, Zheng, & He 2019;Zhang, Zhang, Shi, & Yao 2020). However, while historical records of TC tracks as recorded by geo-spatial location has the potential to yield new insight into TC behaviour, the body of research into TC track spatial geometry and curvature and the evolution of these characteristics post genesis is far less prevalent (Sharma, Magee, & Verdon-Kidd 2021).…”
Section: Introductionmentioning
confidence: 99%